Co-creation strategy in peer-to-peer accommodation in Bandung tourism context - Anna Riana Putriya; Utomo Sarjono Putro; Pri Hermawan; Kyoichi Kijima (BISMA (Bisnis dan Manajemen), 2020)
AbstractCollaborative economy refers to social and economic sharing activities that make entities (customer and peer provider) in-service ecosystem can access services through technology or digital platform. This research aims to give a better understanding of activities and interaction between entities that can potentially elevate the existence of peer-to-peer (P2P) accommodation in Indonesia. Although research regarding the collaborative economy has been accelerating, there has not been a formal conceptualization of interaction from a broadening perspective as a service ecosystem in the context of co-creation. Preliminary study becomes crucial and relevant with the raising of the collaborative economy, based on the consideration that no previous research is considered to be able to explain the dynamics of interaction by using a perspective of Service-Dominant Logic (S-D Logic). This study seeks to answer two research questions, what interactions occur outside consumers, peer providers, platform providers, and how co-creation might be created in the P2P service ecosystem. This conceptual paper draws on the interaction from the perspective of co-creation between entities and stakeholders as a lens by using the systematic-qualitative approach. In general, this study uses the Soft System Methodology (SSM) precisely defining an unstructured situation in the real world. This study tries to initiate the development of phases of co-creation between entities in the service ecosystem. The outcomes of this study enrich the body of knowledge of service science, especially on the way to apply the framework value co-creation. The development of a better service ecosystem across particular engagement remains critical.